Constitutionalizing the Environment in 21st Century Europe: Innovations for Greener Constitutions - Goce Kocevski (Journal of Liberty and International Affairs)
This paper analyzes and systematizes innovations in the constitutional entrenchment of environmental protection provisions, moving beyond the mere recognition of the right to a healthy environment or the affirmation of general policy declarations. Using the comparative constitutional method, it examines relevant provisions in the constitutions of France, Montenegro, Hungary, Austria, and Slovenia. The findings reveal significant diversity in the scope and manner of environmental constitutionalization, contrasting with the similarities observed among constitutions adopted in the 1990s. Identified approaches include the integration of environmental law principles, the constitutional recognition of procedural environmental rights, and the establishment of institutions dedicated to environmental protection. These constitutional innovations demonstrate significant potential for broader adoption, thereby strengthening frameworks for environmental protection and enhancing the safeguarding of human rights and liberties.